Upon a dark night - Lovesey, Peter, 1936- (A Peter diamond mystery, 2014)
A young woman emerges from a coma. Who is she, and why was she dumped unconscious in a hospital car park upon a dark night? She is unable to recall anything, even her name. Then Ada Shaftsbury, a big, boisterous shoplifter she meets in a hostel for the homeless, takes up her cause and gives her the temporary name of Rose.Peter Diamond is already investigating a suspicious death (upon another dark night a woman plunged from the roof of Bath's Royal Crescent) and is unwilling to get involved.Badgered by Ada, galvanised by another gruesome death, Diamond is forced to admit that Rose is the key to the mystery - but she is no longer there.His own dark night is just beginning.